General lifestyle characteristics of students who practice sports - Андрійчук, Ольга Ярославівна; Andriіchuk, Olga Ya. (My University, 2016)
The article deals with the problems of a healthy, balanced eating habits for students who regularly attend classes of physical education (PE). The general features of the daily diet are analyzed. The experiment involved 1,620 students of Lesya Ukrainka Eastern European National University (age ‒ 17-22 years, gender ‒ 1213 female students (74.9%) and 407 male students (25.1%) who regularly attend PE classes. The survey was conducted using the suggested anonymous questionnaire. The study confirms that students usually eat at home or at their relatives, they do not follow a diet that is very important for people who are engaged in exercise regularly. Respondents have the symptoms of digestion disorders. They try to correct their body weight being on a diet.
Keywords: physical education (PE); students; regular meals